2018
DOI: 10.3324/haematol.2017.175216
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage scavenger receptor SR-AI contributes to the clearance of von Willebrand factor

Abstract: Previously, we found that LDL-receptor related protein-1 on macrophages mediated shear stress-dependent clearance of von Willebrand factor. In control experiments, however, we observed that von Willebrand factor also binds to macrophages independently of this receptor under static conditions, suggesting the existence of additional clearance-receptors. In search for such receptors, we focused on the macrophage-specific scavenger-receptor SR-AI. von Willebrand factor displays efficient binding to SR-AI (half-max… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 31 publications
2
38
0
Order By: Relevance
“…We observed a substantial reduction in the titer of total anti-human VWF IgG antibodies in STAB2-KO mice compared with normal involving a number of ligand-receptor interactions including the hepatocyte-and macrophage-expressed asialoglycoprotein receptor, SIGLEC5, SR-A1, and members of the LDL receptor family (12,29,(41)(42)(43)(44). In immunological studies, FVIII has been shown to associate in part with both dendritic cells and marginal zone macrophages in the mouse spleen (10,11), while the binding of FVIII to dendritic cell receptors has been described in vitro (45).…”
Section: Genetic Variability and N-linked Glycans Modulate The Interamentioning
confidence: 84%
“…We observed a substantial reduction in the titer of total anti-human VWF IgG antibodies in STAB2-KO mice compared with normal involving a number of ligand-receptor interactions including the hepatocyte-and macrophage-expressed asialoglycoprotein receptor, SIGLEC5, SR-A1, and members of the LDL receptor family (12,29,(41)(42)(43)(44). In immunological studies, FVIII has been shown to associate in part with both dendritic cells and marginal zone macrophages in the mouse spleen (10,11), while the binding of FVIII to dendritic cell receptors has been described in vitro (45).…”
Section: Genetic Variability and N-linked Glycans Modulate The Interamentioning
confidence: 84%
“…In keeping with the importance of shear, the A1 domain of VWF has been shown to be important in modulating interaction with LRP1 (Wohner et al , ; Chion et al , ). In vitro studies further suggest that additional domains of VWF (including D'D3 and D4) may also contribute to LRP1 binding (Wohner et al , ) (Fig B). Although the molecular mechanisms through which multimeric VWF interacts with the large LRP1 receptor remain poorly understood, plasma VWF levels were significantly increased (1·6‐fold) in mice with macrophage‐specific deficiency of LRP1 compared to controls (Rastegarlari et al , ).…”
Section: Scavenger Receptors and Vwf Clearancementioning
confidence: 97%
“…The scavenger receptor class A member I (SR‐A1; also known as SCARA1 or CD204) is another scavenger receptor expressed in macrophages and DCs (Zani et al , ) (Fig A). Recent in vitro studies have demonstrated that VWF binds to purified SR‐A1 in a dose‐dependent and saturable manner (Wohner et al , ). Similar to LRP1, multiple different domains of VWF have been implicated in regulating SR‐A1 binding (including the D'D3 region, the A1 domain and the D4 domain) (Wohner et al , ) (Fig B).…”
Section: Scavenger Receptors and Vwf Clearancementioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, VWF mutations associated with decreased VWF sialylation [59] and increased binding of VWF to LRP1 and SR-AI [60,61] have been associated with low VWF resembling the type 1 VWD phenotype, but with normal platelet and endothelial VWF [58]. Supporting these observations, large cohort studies have found a significant proportion of type 1 VWD patients with enhanced VWF clearance [39,62,63], which would be an additional mechanism of the disease.…”
Section: Difficulties With Diagnosis Of Type 1vwdmentioning
confidence: 99%